2013
DOI: 10.1002/cpdd.12
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Studies of Cysteamine Bitartrate Delayed‐Release

Abstract: A twice-daily microsphere formulation of cysteamine bitartrate has been developed for cystinosis and other potential applications. To date, there are no published pharmacokinetic data for cysteamine bitartrate delayed-release in healthy adults. Three randomized open-label, crossover studies to determine the effects of fasting, high fat, and carbohydrate meals on the bioavailability of cysteamine bitartrate delayed-release (600 mg) administered in capsule or sprinkle form to healthy adults. Adverse events were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
(96 reference statements)
0
14
0
Order By: Relevance
“…Drug absorption from innovative paediatric solid formulations, which are usually formulated into a hard capsule, such as multiparticulates and minitablets, show less dependency on the time needed for disintegration, compared to the intact formulation. Differences in the pharmacokinetic profiles have been observed after administration of a capsule and sprinkled formulation in the fed state, achieved by the two formulations in an adult study . McLean et al .…”
Section: Food Effects On Oral Drug Absorption In Paediatricsmentioning
confidence: 99%
“…Drug absorption from innovative paediatric solid formulations, which are usually formulated into a hard capsule, such as multiparticulates and minitablets, show less dependency on the time needed for disintegration, compared to the intact formulation. Differences in the pharmacokinetic profiles have been observed after administration of a capsule and sprinkled formulation in the fed state, achieved by the two formulations in an adult study . McLean et al .…”
Section: Food Effects On Oral Drug Absorption In Paediatricsmentioning
confidence: 99%
“…The bioequivalence between administration of intact cysteamine bitartrate DR capsules and beads from opened capsules mixed with food has been demonstrated. 9 This study did not evaluate the effects of various foods and liquids on halitosis, which is a known transient side effect of cysteamine via its metabolite dimethyl sulfide. A halitosis sub-study of a Phase III clinical trial with DR cysteamine bitartrate associated that formulation with a 26% reduction in exhaled dimethyl sulfide in comparison with immediate-release cysteamine bitartrate.…”
Section: Introductionmentioning
confidence: 99%
“…Studies to date have shown that the PK of both immediate release and DR formulations of cysteamine bitartrate are adversely affected by concomitant food intake. In the case of DR capsules, a high-fat meal substantially reduced exposure (as shown by AUC and C max ) and doubled t max compared with fasting administration [ 10 ]. This has justified the recommendation that cysteamine bitartrate be administered in the fasting state and at least 30 min before a carbohydrate-rich meal [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous pharmacokinetic (PK) study determined that optimal absorption of cysteamine bitartrate DR capsules occurs during the fasting state (> 30 min before a carbohydrate-rich meal) [ 10 ]. It is also recommended that cysteamine bitartrate DR be administered with fruit juice (except grapefruit juice) for maximum absorption [ 4 ].…”
Section: Introductionmentioning
confidence: 99%